Terrorismus Akteure, Strukturen, Entwicklungslinien - Riegler, Thomas (Studien Verlag, 2009)
"Terrorism. 9/11 in Context" is an anthology of thematic priorities that aims to establish a better understanding of the complexities of terrorism aside from one-dimensional characterisations in media and politics. The main focal points are: The definition of terrorism, its causes, mythological charging and pop cultural realization. Reactions of the state towards the terrorist challenge - the political, military and security aspects as well as media counter strategies - are also of keen interest. Further, as case-studies from the US, Latin America and Europe clearly demonstrate the state can also be a perpetrator of terrorism, either during covert operations or by adopting the mirror image of guerrillas and terrorists in counter insurgency warfare. The main thread of "Terrorism. 9/11 in Context" is the analysis of the "superstructure"- the symbolic and ideological sources of terrorism. Terrorist violence is seen as commitment for radical political change, which is fuelled not only by political and social grievances, but also by the gratification of a radical-action identity. Thus, terrorism is most of all the product of a powerful idea, which motivates and stimulates activists, giving them the strong conviction needed to follow through their "project". It's the idea that not only is it possible to wage resistance against an alleged illegitimate, corrupt authority; it is also possible to inspire others to participate in an avant-garde armed struggle. On the other hand, the perspective of politicians and authorities on the terrorist enemy is also influenced to a certain degree by imagination and projection - this process is analysed through the depiction of terrorism in cinema, media and the imitation of terrorist tactics by counter terrorism forces.